Tables for the hydraulic design of pipes, sewers and channels. Volume 2 - Wallingford, H. R. (Thomas Telford, 2006)
This book is the second of two self-supporting volumes that make up the 8th edition of 'Tables for the Hydraulic Design of Pipes, Sewers and Channels'. It provides an alternative solution system for the Colebrook-White equation.
Keywords: Drainage pipes -- Design -- Tables.; Channels (Hydraulic engineering) -- Tables.; elektronické knihy; electronic books